2024
DOI: 10.1002/adfm.202315006
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Riveting Structure for High Power and Long Lifespan Potassium‐Ion Batteries

Zhen‐Duo Liu,
Xuan‐Wen Gao,
Jian‐Jia Mu
et al.

Abstract: The development of potassium‐ion batteries (KIBs) relies on the exploration of stable layer‐structured oxide cathode materials and a comprehensive understanding of ion storage and diffusion behaviors. A multiphase riveting‐structured O3/P2/P3‐Na0.9[Ni0.3Mn0.55Cu0.1Ti0.05]O2 (Tri‐NMCT) is employed as cathode material for KIBs. It demonstrates an initial discharge specific capacity of 108 mA g−1 at current density of 15 mA g−1 in the voltage range of 1.5–4 V. Excellent cyclic stability is exhibited as well with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…As the discharging continues, the K + /Na + mixed phase (P2-K/Na) appeared at 15.3° and 30.6°, consistent with previous reports. 36 According to inductively coupled plasma mass spectroscopy (ICP-MS) results (Table S3†), the atomic ratio of K, Na, Ni, and Mn was identified to be 0.43 : 0.34 : 0.22 : 0.66. Ex-situ XRD tests of various cycled electrodes at the end of discharge were carried out to further analyze the structural change (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the discharging continues, the K + /Na + mixed phase (P2-K/Na) appeared at 15.3° and 30.6°, consistent with previous reports. 36 According to inductively coupled plasma mass spectroscopy (ICP-MS) results (Table S3†), the atomic ratio of K, Na, Ni, and Mn was identified to be 0.43 : 0.34 : 0.22 : 0.66. Ex-situ XRD tests of various cycled electrodes at the end of discharge were carried out to further analyze the structural change (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This process was repeated within a voltage window of 1.5–4.0 V. During the titration process, a linear relationship can be established between the battery voltage and τ 1/2 , whereby the chemical diffusion coefficient of K + in the electrode can be determined using the following equation (eqn (2)). 52 …”
Section: Methodsmentioning
confidence: 99%
“…As discussed above, the role of Mg 2+ or Ti 4+ in the partial substitution of Mn 3+ is to effectively maintain a single-phase reaction and improve the cycling stability. 64,173,189 This also applies to multi-element electrodes. Both P3-type K 0.45 Co 1/12 Mg 1/12 Mn 5/6 O 2 and P3-type K 0.4 Fe 0.1 Mn 0.8 Ti 0.1 O 2 have been demonstrated as cathode materials for PIBs with high structural reversibility.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Xu et al 192 found that partial replacement of O 2− with F − could extend the interlayer distance of K 2/3 Mn 7/9 Ni 1/9 Ti 1/9 O 2 and counteract their capacity fading at high voltage (>4.0 V vs. K + /K). Recently, Liu et al 64 prepared a multiphase riveted structure O3/P2/P3-Na 0.9 [Ni 0.3 Mn 0.55 Cu 0.1 Ti 0.05 ]O 2 (Tri-NMCT) as a PIB cathode material. Among them, the O3 phase and P3 phase serve as the main storage sites for K + .…”
Section: Cathode Materialsmentioning
confidence: 99%